Overview of Parental Stimulation on Language Development in Toddler - Luthfi Akmal Fauzi; Ulfa Azizah (UM Purwokerto Press, 2026)
This study aims to understand the overview of parental stimulation on the language development of toddlers in Majatengah Village, Purbalingga Regency. Stimulation is provided by parents, caregivers, or others close to the child, such as family members and the surrounding environment in daily life. Language development begins in infancy, relying on experiences, language acquisition, and growth, progressing systematically as the child ages. Using a quantitative, descriptive research method with a survey approach, the study provides insights into parental stimulation related to language development in toddlers. The results indicate that the language development of toddlers in Majatengah Village is generally good. A good educational background appears to influence parents' understanding of the importance of language stimulation in child development.